2021
DOI: 10.2166/wpt.2021.091
|View full text |Cite
|
Sign up to set email alerts
|

Chemical deposition of iron nanoparticles (Fe0) on titanium nanowires for efficient adsorption of ciprofloxacin from water

Abstract: The development of antimicrobial resistance genes (AMRs) in water was globally accelerated due to the occurrence of ciprofloxacin (CIP) in water. This study aims to precipitate iron nanoparticles (Fe0) on the surface of titanium nanowires (TNWs) through a chemical process to overcome the limitations of Fe0 and efficiently remove CIP from water. TEM and XRD results confirmed the successful synthesis of Fe0 and TNWs. They also proved the successful deposition and dispersion of Fe0 on TNWs. Several (Fe0/TNW) nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Moreover, the magnitude of enthalpy change (ΔH = 145.69 kJ/mol) suggested that the removal mechanism also involves a chemisorption process, which can be attributed to As(V) reduction to As(III) and the possible co-precipitation of As(III) with the released Fe 2+ . The initial concentration effect on As(V) removal by nFe 0 @Mg(OH)2 was studied considering different values (5,10,20, and 40 mg/L). The results clearly indicated the potential of nFe 0 @Mg(OH)2 to satisfactorily remove As(V), even at extreme As(V) concentrations, where it exhibited final removal efficiency of around 88% of 40 mg/L initial As(V) concentration (Fig.…”
Section: As(v) Removal Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the magnitude of enthalpy change (ΔH = 145.69 kJ/mol) suggested that the removal mechanism also involves a chemisorption process, which can be attributed to As(V) reduction to As(III) and the possible co-precipitation of As(III) with the released Fe 2+ . The initial concentration effect on As(V) removal by nFe 0 @Mg(OH)2 was studied considering different values (5,10,20, and 40 mg/L). The results clearly indicated the potential of nFe 0 @Mg(OH)2 to satisfactorily remove As(V), even at extreme As(V) concentrations, where it exhibited final removal efficiency of around 88% of 40 mg/L initial As(V) concentration (Fig.…”
Section: As(v) Removal Resultsmentioning
confidence: 99%
“…nFe 0 was prepared via the chemical reduction of FeCl3 precursor by NaBH4 reductant, following the exact synthesis conditions reported in our previous work [19][20][21]. nFe 0 @Mg(OH)2 was synthesized by the thermal deposition of Mg 2+ precursor on nFe 0 surface via OHlinking within ethanol medium at 50 ± 1.0 °C [16,22].…”
Section: Materials Synthesismentioning
confidence: 99%
“…With the rapid increase in the human population and farm animals, use of antibiotics has increased all over the world. This results in a significant increase in antibiotic load in surface waters [14,15]. CIP has been found in drink-ing water (0.032 µg L −1 ), lake water (6.5 mg L −1 ) [16], sewage (11-99 µg L −1 ) [17], hospital wastewater (150 µg L −1 ) [18], and pharmaceutical industry effluent (31-50 mg L −1 ) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Residues of antibiotics are released to the environment through the effluents of domestic, industrial, and hospital wastewater treatment plants, landfill sites, various veterinary applications (e.g., aquaculture, poultry and livestock farms, etc. ), and so forth [6,7]. Despite the great benefits in the human and veterinary medicine, the persisting and bioaccumulation of antibiotics in the environment especially the limited water resources are suspected of causing serious health and ecological issues.…”
Section: Introductionmentioning
confidence: 99%
“…), emulsification, oxidant addition (i.e., hydrogen peroxide), and organic ligands addition (e.g., oxalate, etc.) [7,20,21]. Our previous article demonstrated that the adding 0.3 mM of the organic ligan oxalate to 0.3 g L -1 of Fe 0 nanoparticles enhanced the adsorption of CIP from 45.04% (Fe 0 ) to 95.74% (Fe 0 /oxalate) [4].…”
Section: Introductionmentioning
confidence: 99%